Analysis of Islamic boarding school students' higher-order thinking skills in number topics based on Bloom's revised taxonomy - Mufarrido Husnah; Jarnawi Afgani Dahlan; Dadan Dasari; Tatang Herman (State Islamic University of North Sumatra, 2026)
This study aimed to analyze the Higher Order Thinking Skills (HOTS) of Islamic boarding school students in number topics, specifically number factorization, Least Common Multiple (LCM), and Greatest Common Factor (GCF), based on Anderson’s cognitive taxonomy. The study employed a qualitative descriptive approach, using three questions designed to measure higher-order thinking skills at the analysis (C4), evaluation (C5), and creation (C6) levels. The research sample consisted of 22 Islamic boarding school students who were selected using stratified random sampling. The results of the analysis showed that students' abilities in the aspects of analysis and evaluation were quite good, while their abilities in the aspect of creation were still low. Most students were categorized as having moderate and low levels of ability based on the scores obtained. These findings indicated the need for more focused and innovative learning strategies to promote the development of students' HOTS, especially in the context of Islamic boarding schools, which had limited time allocated for general subjects. This study recommended the integration of more challenging and creative learning approaches to improve the quality of students' higher-order thinking skills.